Attenuation of Microcystins Using Electron Beams and Gamma Radiation: A Study with Environment-Bound Conditions - Joao Dias Toledo Arruda-Neto; Erika Cavalcante-Silva; Henriette Righi; Odete Rocha; Maria do Carmo Bitten court-Oliveira; Micheline K. Cordeiro-Araújo (Journal of Experimental and Clinical Toxicology, 2021)
Microcystins (MCs) are toxins profusely synthesized by cyanobacteria, causing livestock poisonings and endangering human health. We design and execute an experiment to investigate the attenuation (degradation) of microcystins by exposing them to gamma radiation and electron beams at doses of 0 (control), 3, 5, 10 and 15 kGy. The experimental conditions simulate microcystin contamination of aquatic environments; we thus consider (1) microcystins inside whole cells and extracellular dissolved in water, simulated by non-sonicated and sonicated cells, respectively, and (2) two acute microcystin concentrations within water. Toxicity tests of Microcystis aeruginosa detected immobilization (i.e., paralysis) of Ceriodaphniasilvestrii exposed to aqueous crude extracts of irradiated and non-irradiated M. aeruginosa (NPLJ-4 strain) at concentrations of 45 and 90 mg.L-1 (mg dry weight of freeze-dried material), and the results were analyzed using the Trimmed Spearman-Karber statistical program to obtain 48-h EC50, the average effective concentration causing immobility in 50% of organisms after 48 hours. We conclude that electron beams are effective physical agents for toxin attenuation (degradation) and reach 100% effectiveness at 5 kGy and above; their efficiency is two orders of magnitude greater than that of gamma radiation. This new body of information contributes to (1) remediating environmental water sources; (2) designing water/wastewater treatment facilities; (3) combatting chronic microcystin environmental contamination; and (4) inspiring further studies to promote the use of biomonitors (e.g., Cladocerans) to detect and evaluate microalgae contamination.
Keywords: Microcystin